2015
DOI: 10.1352/1944-7558-120.4.273
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Intelligence, Visual-Motor Functioning, and Personality Characteristics With Adaptive Behavior in Individuals With Williams Syndrome

Abstract: Williams syndrome (WS) is associated with deficits in adaptive behavior and an uneven adaptive profile. This study investigated the association of intelligence, visual-motor functioning, and personality characteristics with the adaptive behavior in individuals with WS. One hundred individuals with WS and 25 individuals with developmental disabilities of other etiologies were included in this study. This study found that IQ and visual-motor functioning significantly predicted adaptive behavior in individuals of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Porter et al (2009), who studied primarily adolescents and adults, also found only one significant correlation – a negative correlation with Externalizing Problems T-score. Fu (2012), who studied primarily adults, did not report any significant correlations with CA.…”
Section: Prior Child Behavior Checklist Findings: Individuals With Wsmentioning
confidence: 80%
See 3 more Smart Citations
“…Porter et al (2009), who studied primarily adolescents and adults, also found only one significant correlation – a negative correlation with Externalizing Problems T-score. Fu (2012), who studied primarily adults, did not report any significant correlations with CA.…”
Section: Prior Child Behavior Checklist Findings: Individuals With Wsmentioning
confidence: 80%
“…All of these studies were cross-sectional. Studies are ordered by the approximate mean chronological age (CA) of the sample, which ranged from 5.13 years for Papaeliou et al (2012) and 6.13 years for Fidler et al (2000) to 18.16 years for Porter et al (2009) and 28.23 years for Fu (2012; Fu et al, 2015). Note that although the last three studies in the table included adults in their samples, the oldest age for which the CBCL is normed is 18 years.…”
Section: Prior Child Behavior Checklist Findings: Individuals With Wsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies show that WS performances correspond to MA (Georgopoulos et al ; Pezzini et al ) but seem not to exceed the scores shown by the 5‐year‐old typically developing (TD) children (Bellugi et al ; Dykens et al ; Pagon et al ). The WS performances on the VMI are also reported to be significantly lower than those of their peers with Down syndrome (Wang et al ) or an intellectual deficiency of a non‐specific origin (Fu et al ). However, authors observed that the majority of participants with WS correctly copy simple geometric shapes (e.g.…”
Section: Introductionmentioning
confidence: 99%